EFFICIENCY TESTING OF EXPERIENTIAL ESP INSTRUCTION TO FUTURE SYSTEM ANALYSTS - Z. М. Kornieva; I. V. Pavlovska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2015)
The article deals with the topical problem of introducing the experiential methodology into the process of teaching English at technical tertiary schools. The backgrounds of the methodology mentioned are analyzed; the process of implementing the general and narrow professionalization into English instruction is described. GeneralEnglishprofessionalization aims atsimultaneouscombinationofseveralelementsofteaching, whicharetaughtseparatelyunderthecurrentcurriculumandalso have separate timeallocation. These components include the improvement of general English competence, as well as general and narrow professionalization of English instruction. The authors describe the stages of efficiency testing of experiential ESP instruction using the new textbook "Professional Basics". The study is suggested to be organized on the basis of the aspected approach, which stresses the necessity in studying such components as subject, sociolinguistic, linguistic, psychological and communicative aspects. The factual results of the experiment and estimation of the proposed methodology efficiency are given. It is stated that the textbook and the methodology proved their high efficacy in learning outcomes - all groups showed the general increase in all types of communicative activities. The outcomes of the questionnaires completed by the students after the experimental study under the proposed methodology are also presented.